Palliative care for people with schizophrenia: A qualitative study of an under-serviced group in need - McNamara, Beverley; Same, A.; Rosenwax, L.; Kelly, B. (2018)
Â© 2018 The Author(s). Background: People with schizophrenia are at risk of receiving poorer end of life care than other patients. They are often undertreated, avoid treatment and are about half as likely to access palliative care. There are limited options for end of life care for this under-serviced group in need. This study aims to address the paucity of research by documenting possible need, experiences of health care service use and factors affecting palliative care use for people with schizophrenia who have advanced life limiting illness. Methods: Semi-structured interviews were undertaken with 16 experienced health professionals caring for people with schizophrenia in Western Australia. The interviews focussed on their perceptions and experiences of end of life care, their patients' unmet needs, palliative care options, and suggested services to support this vulnerable group and improve health care provision. The research used a qualitative design and thematic analyses. Results: The participants all advocated strongly for their patients and recognised their extreme vulnerability. They identified a range of challenges and unmet needs experienced by people with schizophrenia at the end of life including: illness factors such as the impact of schizophrenia on information processing and communication; social factors such as stigma, isolation and the absence of a carer; and health care factors such as late diagnosis, delayed access to care, and mismanagement in care. Four themes were organised into two domains with the first exploring the individual and social circumstances of people with schizophrenia, including the challenges they experience in the health care system. The second domain covers themes that discuss barriers and facilitators to people with schizophrenia receiving palliative care and key features in palliative care provision, including recognising declining health, communication and planning, and collaboration and capacity building in the broader health, mental health and palliative care sectors. Conclusions: To ensure people with schizophrenia are well supported at the end of life a model of palliative care is required that offers both specialised services and capacity building within the pre-existing health workforce. Resources are needed to address the stigma and lack of services faced by this vulnerable group.